A prática como lócus de formação de professores e produção de saberes na Educação Física - Silva, Mellissa Fernanda Gomes da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research has as objective to understand how professional practice, while locus of training and knowledge production can contribute to the construction of an epistemology of professional practice. Specifically sought to: a) analyze specific bibliographic sources about the concept of epistemology of professional practice; b) investigate how the didátic-pedagogical experience contributes to think professional practice as a locus of training in Physical Education; c) identify the knowledge that underlie the professional practice in the representation of teachers, and; d) analyze the extent to which teaching (factors, determinants, requirements, conditions, etc.) influences the construction of the epistemology of professional practice in Physical Education. The methodological procedures was based for a qualitative research, analytical descriptive, using as data collection questionnaire and a semi-structured interview. Data analysis was guided by content analysis of questionnaires and interviews collected from 18 teachers of Physical Education, State Schools belonging to the Board of Education of Limeira. Data were organized into two chapters, in which the first dealt with the teaching knowledge, while the second dealt about practical rationality. Regarding knowledge was observed in answers an amalgamation of professional knowledge composed of a temporal nature; a plural and heterogeneous nature, and; a human, personalized and situated nature (TARDIF, 2012) highlighting the manifestation of a cultural capital (BOURDIEU, 1979) and a biographical and relational process regarding the identity issue knowledge (DUBAR, 2005). Among other aspects pointed to the diversity of knowledge that assist in performing the tasks inherent in the teaching work and the human dimension of this knowledge in what refers to the object of this work. With regard to the practical rationality, critical reflection possible to analyze the teaching culture at work...

Esta pesquisa teve como objetivo geral compreender como a prática profissional, enquanto lócus de formação e produção de saberes pode contribuir para a construção de uma epistemologia da prática profissional. Especificamente buscou: a) analisar fontes bibliográficas específicas acerca do conceito de epistemologia da prática profissional; b) investigar como a experiência didático-pedagógica contribui para se pensar a prática profissional como lócus de formação na Educação Física escolar; c) identificar os saberes que fundamentam a prática profissional nas representações dos professores, e; d) analisar em que medida o trabalho docente (fatores, determinantes, exigências, condições, entre outros) influencia na construção da epistemologia da prática profissional na Educação Física escolar. A epistemologia da prática profissional foi compreendida neste estudo como sendo os saberes que os professores de Educação Física realmente utilizam na realização do trabalho docente (TARDIF, 2012). Como procedimentos metodológicos optou-se pela pesquisa qualitativa, descritiva analítica, utilizando como instrumento de coleta de dados o questionário e a entrevista semiestruturada. O tratamento dos dados pautou-se pela análise de conteúdo dos questionários e dos depoimentos colhidos de 18 professores de Educação Física da Rede Estadual de Ensino pertencentes à Diretoria de Ensino de Limeira. Os dados foram organizados em dois capítulos, no qual o primeiro tratou dos saberes docentes, enquanto que o segundo tratou sobre a racionalidade prática. Com relação aos saberes observou-se nas respostas uma amálgama de saberes profissionais composta de uma natureza temporal; uma natureza plural e heterogênea, e; uma natureza humana, personalizada e situada (TARDIF, 2012) com destaque para a manifestação de um capital cultural (BOURDIEU, 1979) e de um processo biográfico e relacional no tocante a questão identitária...
Keywords: Teachers, Training of; Professores - Formação; Pratica de ensino; Prática profissional; Epistemologia; Educação física - Estudo e ensino